RANCANG BANGUN SISTEM INFORMASI ADOPSI KUCING BERBASIS WEBSITE STUDI KASUS PADA (OMAHKOECING) - Jowanka, Axzara Wirid Isra; Oktaviani, Intan; Muhtarom, Moh. (Infotech: Journal of Technology Information, 2024)
Animal adoption is the process in which a person or family takes on the responsibility of caring for a pet that previously did not have a permanent home. Because the cat adoption process in OmahKoecing is still manual and the available information only relies on one social media platform, namely Instagram, this research aims to evaluate the effectiveness of the website-based adoption system compared to previous methods, both in terms of increasing the number of successful adoptions, as well as in terms of user satisfaction with a more transparent and structured adoption process and also increases the ease of the adoption process. This system is designed to simplify the adoption process via the website by providing complete and clear information for potential adopters. Researchers conducted an analysis of system weaknesses to strengthen the results of data that had been collected through interviews with the owner of OmahKoecing, direct observation, and literature study. The research uses a prototype method which involves several stages, namely communication, planning, design and implementation. The research results show that this system facilitates the adoption of abandoned animals, especially cats by providing a letter of agreement feature that helps ensure the adopter's seriousness about the animal they are going to adopt. This shows that the prototype method is very helpful in developing a cat adoption system.ABSTRAKAdopsi hewan adalah proses di mana seseorang atau keluarga mengambil tanggung jawab merawat hewan peliharaan yang sebelumnya tidak memiliki rumah tetap. Karena proses adopsi kucing di OmahKoecing masih manual dan informasi yang tersedia hanya mengandalkan satu platform media social yaitu instagram, penelitian ini bertujuan untuk mengevaluasi efektivitas sistem adopsi berbasis website dibandingkan dengan metode yang ada sebelumnya, baik dari segi peningkatan jumlah adopsi yang berhasil, maupun dari segi kepuasan pengguna terhadap proses adopsi yang lebih transparan dan terstruktur dan juga meningkatkan kemudahan dalam proses adopsi. Sistem ini dirancang untuk mempermudah proses adopsi melalui website dengan menyediakan informasi lengkap dan jelas bagi calon pengadopsi. Peneliti melakukan analisis kelemahan sistem untuk menguatkan hasil data yang telah dikumpulkan melalui wawancara dengan pemilik OmahKoecing, observasi langsung, dan studi literatur. Penelitian menggunakan metode prototype yang melibatkan beberapa tahapan yaitu komunikasi, perencanaan, perancangan, dan implementasi. Hasil penelitian menunjukkan bahwa sistem ini memfasilitasi adopsi hewan terlantar, khususnya kucing dengan menyediakan fitur surat perjanjian membantu memastikan keseriusan pengadopsi terhadap hewan yang akan mereka adopsi. Ini menunjukkan bahwa metode prototype sangat membantu dalam pengembangan sistem adopsi kucing.